Women Potters at Sambirata in Ecofeminism Perspective - Koniherawati (East Asian Journal of Multidisciplinary Research, 2022)
The Majority of pottery makers in Sambirata Village, Purbalingga Regency, Central Java are middle-aged women. Although their activities as pottery is often seen by community as a side job, in reality, it continues to exist amid competition for modern household equipment made of metal and plastic. The money that these middle-aged women pottery makers earn is more reliable as aroutine source of family income, compared to the work of their hisbands who work seasonally as farm labourers. In addition, pottery makers in Sambirata usually use the non-productive rice field in their village to get the raw material for making pottery. Here we see the peculiarity of this research, namely women who in Javanese culture are often considered as domestic workers are in fact capable of supporting their family and create a new value upon an unproductive rice field. Through qualitative research with participatory observation, researcher found the factors that made these women able to survive amidst modernity challenges.